Exergoeconomic analysis and determination of power cost in MCFC – steam turbine combined cycle - Sartori da Silva, Fellipe [UNESP]; Matelli, José A. [UNESP] (Elsevier, 2019)
A novel combined molten carbonate fuel cell – steam turbine based system is proposed herein. In this cycle, steam is produced through the recovery of useful heat of an internal reforming MCFC and operates as work fluid in a Rankine cycle. Exergoeconomic analysis was performed, in order to verify the technical feasibility, including which components could be improved for greater efficiencies, as well as the cost of the power generated by the plant. A 10 MW MCFC was initially proposed, when the system reached 54.1% of thermal efficiency, 8.3% higher than MCFC alone, 11.9 MW of net power, 19% higher than MCFC alone, and an energy cost of 0.352 $/kWh. A sensitivity analysis was carried out and the parameters that most influenced on the cost were pointed out. The analysis pointed to the MCFC generation as the most impactful factor. By manipulating these values, it could be noted a significant power cost decrease, reaching satisfactory values to become economically feasible. The concept of economy of scale could be noticed in the proposed system, proving that a large-scale plant could be the focus of investment and public policies.
Keywords: Exergoeconomic analysis; Molten carbonate fuel cell; Power cost